Correlation Between Nutritional Status of Lactating Mothers With The Composition of Breast Milk and The Growth of Babies In Selected Samples - Siti Dawiesah Ismadi, Siti Dawiesah Ismadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1975)
key words: lactating, breast milk